Characterization of the competitive strength of men's artistic gymnastics in China - Cheng, Guangxin; Yang, Hechong (Quality in Sport, 2024)
Introduction and purpose：The 2022 National Gymnastics Championships men's artistic gymnastics competition was examined and analyzed in order to assess the competitive strength of China's men's artistic gymnastics under the new regulations. The analysis included a review of China's men's artistic gymnastics problems and current performance status, as well as suggestions for strengthening the sport. Materials and methods:Using the literature method—searching and analyzing through the CNKI, WOS, library, and other databases—as well as the observation method and mathematical and statistical techniques for statistical analysis of the athletes competing in the various regions and units, as well as field research and study methods involving video and on-site game observation—first-hand information was obtained for this paper's theoretical support. Conclusions: men's artistic gymnastics in China is not developing regionally, with strong regions in the south and weak regions in the north, as well as strong and weak regions in the east and west;These disparities in the sport's development also affect athletes' overall competitive strength, with athletes in various sports having wide disparities in their scores and failing to create a supportive environment for competition, particularly in individual all-around , pommel horse, rings, and horizontal bars projects;Additionally, China's men's artistic gymnastics athletes' age structure needs to be further optimized. It is necessary to continue executing the preparatory plan of mending the short boards and strengthening the strong items.